Penerapan Sikap Profesionalisme Auditor pada Pemeriksaan Aset dan Kas KAP Rudiana Fibriani - Naufal Maulana Waluyo; R Muh Syah Arief Atmaja (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The research objective is to evaluate the effectiveness of the audit process in ensuring the accuracy and completeness of financial statements and identifying the role of auditors in increasing the transparency and credibility of the company. The research method used is descriptive with an exploratory approach. The audit process involves four main stages: planning and designing the audit approach, testing controls and transactions, performing analytical procedures and detailed testing of balances, and completing the audit and issuing an audit report. The results show that a systematic and competent audit process can identify errors and irregularities in financial statements, improving the quality of information presented to users. Auditor professionalism, which includes competence, independence, and adherence to a code of ethics, plays an important role in conducting audits. Auditors from KAP Rudiana Febriani effectively check internal controls, conduct physical verification of fixed assets, and ensure the validity of proof of asset ownership. Audit as a tool to improve accountability and transparency in the company's financial management. Suggestions are given to improve auditors' training and professional development to ensure they remain competent and able to overcome challenges in the audit process.